The Problem of the Rock and the Grammar of Consciousness - Brons, Lajos (2017)
The “Problem of the Rock” (PoR) is a famous objection to Higher-Order (HO) theories of consciousness. According to PoR, the HO theorists’ claim that a mental state is conscious iff there is a higher-order mental state about it implies that a rock is also conscious iff there is a higher-order mental state about it. In this paper I show that this argument confuses two grammatically distinct attributions of consciousness, and that if the consequent equivocation fallacy is avoided, PoR is either a straw man argument or has an unproblematic conclusion.